2020
DOI: 10.1088/1758-5090/ab7de0
|View full text |Cite
|
Sign up to set email alerts
|

A novel waterborne polyurethane with biodegradability and high flexibility for 3D printing

Abstract: Three-dimensional (3D) printing provides a new approach of fabricating implantable products because it permits a flexible manner to extrude complex and customized shapes of the tissue scaffolds. Compared with other printable biomaterials, the polyurethane elastomer has several merits, including excellent mechanical properties and good biocompatibility. However, some intrinsic behavior, especially its high melting point and slow rate of degradation, hampered its application in 3D printed tissue engineering. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…The use of WBPUUs with different compositions as printing inks for DIW 3D printing has been reported in the literature in the last years, mostly focused on biomedical applications [9,11] In a recent work, Feng et al synthesized a biodegradable WBPUU modified with an amino acid, presenting good flexibility and biocompatibility with a potential application in tissue engineering via 3D printing [12]. In another study, Hsieh et al examined the viability of a thermoresponsive WBPUU that formed a gel near 37 • C without any cross-linker.…”
Section: Introductionmentioning
confidence: 99%
“…The use of WBPUUs with different compositions as printing inks for DIW 3D printing has been reported in the literature in the last years, mostly focused on biomedical applications [9,11] In a recent work, Feng et al synthesized a biodegradable WBPUU modified with an amino acid, presenting good flexibility and biocompatibility with a potential application in tissue engineering via 3D printing [12]. In another study, Hsieh et al examined the viability of a thermoresponsive WBPUU that formed a gel near 37 • C without any cross-linker.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the degradation rate of scaffolds matches the production rate of ECM, whilst the degradation products have no side effects on the host (Sabir et al, 2009). For example, the mass loss of a waterborne polyurethane scaffold reached 35.62% after 90 days of degradation, while the fluorescence image showed that after 7 days of incubation, rabbit chondrocytes covered all waterborne polyurethane scaffolds (Feng et al, 2020). (5) Surface characteristics: The interface between the scaffold and the tissue to be repaired is critical to the success of a scaffold transplantation, with numerous reactions and interactions taking place.…”
Section: Property Requirements Of Bioinks/scaffoldsmentioning
confidence: 99%
“…It has been widely applied in such fields as marine anti-fouling coatings and metal coatings, radioactive materials, drug-delivery systems, biomedical engineering scaffolds, implantable bioelectronics and so on. [10][11][12] Furthermore, biodegradable materials are a type of materials, which are friendly to the environment and have shown good effects on maintaining a controlled-release performance. [13][14][15][16] For example, fertilizers coated with biodegradable materials can improve the nutrient absorption and avoid the nutrient diversion loss during the process of degradation.…”
Section: Introductionmentioning
confidence: 99%